The effect of altitude above sea level on some qualitative and quantitative characteristics of castor leaves and seeds in two locations in Latakia Governorate. (Journal of Hama University, 2025)
This study was conducted in the laboratories of the Faculty of Environmental and Agricultural Sciences and Research at Tishreen University in 2021 with the aim of studying some qualitative and quantitative characteristics of castor leaves and seeds, collected from two different sites in Latakia Governorate [Al-Ramel Al- janobi (Latakia), Khirbet Hishon (Al-Haffa)] due to the importance of this plant from a Medical and industrial standpoint. The research aimed to study some qualitative and quantitative characteristics of castor leaves and seeds in two different locations in Latakia Governorate (chlorophyll a, chlorophyll b, total chlorophyll, carotene, total carbohydrates, total protein, fixed oil, crude fiber, total ash, moisture).The results showed that the site of Khirbet Heshon (Al-Haffah) (the highest above sea level) was significantly superior in all qualitative characteristics studied in castor seeds {carbohydrate (34.263 mg/g), protein (19.95%), fixed oil (54%), and total fiber (17.383%), total ash (19.47%), and moisture (7.542%)}, on the Al- Ramel Al- janobi site. This may be attributed to the environmental conditions suitable for the growth and development of the castor plant.The chemical composition varied significantly in the content of castor leaves according to the sites {Khirbet Heshon with the percentage of chlorophyll a (0.547 mg/g), the percentage of chlorophyll b (0.514 mg/g), the percentage of total chlorophyll (1.199 mg/g), carotene (0.268 mg/g), and carbohydrates (16.12 mg/g), protein (18.71%), phenol (22.71%), moisture (69.812%), and the Al Ramel Al janobi location with total fiber percentage (15.1%) and total ash (12.79%)}.
Keywords: castor; chlorophyll; carotene; carbohydrates; protein; fixed oil